The Benefits and Challenges in Learning English Through Quizwhizzer - Christian Siregar; Fenny Yutika Seli (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Quizwhizzer is one of the ICT tools that can bring positive impacts on students' performance. On the other hand, since Quizwhizzer contains game elements, it potentially distracts students from the learning process, and teachers and students face several challenges when utilizing it in the classroom. In line with these issues, the present study aims to investigate the benefits and challenges of learning English through Quizwhizzer, as well as to uncover suggestions for overcoming these challenges. To address these issues, a mixed method was used and collected data through observation, open-ended questionnaire and interview over 4 months. Our sample of participants studies in a public school particularly SMPN 189 Jakarta. This study took the data from one classroom from the seventh grade students. 33 students who had participated in answering an open-ended questionnaire and 5 students who had participated in an interview. The findings in general revealed that Quizwhizzer can bring positive impacts in learning English, which are increasing students’ motivation (59%), reducing time consumption (34%) and interaction (7%). Furthermore, there are several challenges with the use of Quizwhizzer which are related to the lack of infrastructure (83%) and training (17%). The findings suggest the importance of providing good infrastructure (81%) and training (19%) for students and teachers to overcome the problems. The study offers theoretical insights for educators seeking to integrate Quizwhizzer into language learning.